Evaluation of technological properties, microstructure and predictive glycaemic response of durum wheat pasta enriched with psyllium seed husk. (November 2021) - Renoldi, Niccolò; Brennan, Charles Stephen; Lagazio, Corrado; Peressini, Donatella
Abstract: Psyllium seed husk (PSH) is a soluble dietary fibre with interesting health benefits, including reduction in blood glucose level in subjects with type 2 diabetes. Its supplementation in pasta represents a challenge due to a negative impact of high PSH levels on product acceptability. The aim of this work was to investigate the effects of the substitution of semolina with different levels of PSH on cooking properties, microstructure and in vitro glycaemic response of pasta. Dry pasta samples enriched with PSH were produced by replacing durum wheat semolina with 25, 50, 75 and 100 g/kg PSH. Cooked enriched pastas were firmer and sticker than the control. Cooking loss increased with increasing PSH levels above 25 g/kg with values below the technological acceptable limit of 80 g/kg. Semolina substitution with 50–100 g/kg psyllium was effective in lowering the predictive glycaemic response of enriched pasta in comparison with the control. Scanning electron microscopy and dough rheology (dynamic frequency and temperature sweep tests) suggested that this decrease was related to the formation of fibre aggregates limiting starch swelling. Semolina replacement with 50 g/kg PSH has the potential to provide a health benefit with minimal impact on cooking features of functional pasta. Highlights: Cooked psyllium-enriched pasta showed a more compact structure of gelatinised starch. Cooked pasta containing psyllium was firmer than the control. Psyllium addition at 50–100 g/kg lowered predictive glycaemic response of pasta. Glycaemic response of pasta is related to the swelling degree of starch granules.